Deglaciation chronology of the Donegal Ice Centre, north‐west Ireland. (11th December 2018) - Wilson, Peter; Ballantyne, Colin K.; Benetti, Sara; Small, David; Fabel, Derek; Clark, Chris D.
ABSTRACT: During the Last Glacial Maximum, Donegal in north‐west Ireland functioned as an independent centre of ice dispersal that separated and fed into the Donegal Bay Ice Lobe (sourced in the Irish Midlands) to the south and the Hebrides/Malin Sea Ice Stream to the north. We report geochronological data that demonstrate marked contrasts in the timing and rate of deglaciation in northern and southern Donegal. In northern Donegal, which occupied an inter‐ice‐stream/lobe location, decoupling from the Hebrides/Malin Sea Ice Stream resulted in formation of a marine embayment along the north coast by ∼22–21 ka, and subsequent slow (∼4 ± 1 m a −1 ) climatically driven inland retreat of the ice margin to mountain source areas by ∼17 ka. By contrast, in southern Donegal, which lay near the axis of the Donegal Bay Ice Lobe, deglaciation was delayed until ∼18 ka following readvance of ice to a moraine in outer Donegal Bay. The ice margin subsequently underwent net retreat, apparently uninterrupted by readvances, at a net rate of ∼ 18 ± 6 m a −1 . A mean terrestrial cosmogenic nuclide age of ∼15.0 ka obtained for samples from the foothills of the Blue Stack Mountains in south‐east Donegal indicates that ice persisted in valley heads and cirques at the beginning of the Lateglacial Interstadial, suggesting that these and nearby mountains supported the last remnants of the Irish Ice Sheet before complete deglaciation of Ireland, and that almost all the shrinkage of the ice sheet in this sector occurred under stadial conditions before the onset of interstadial warming at ∼14.7 ka.